Hepatitis C virus cascade of care among people who inject drugs in Australia: Factors associated with testing and treatment in a universal healthcare system. (1st November 2021) - Gibbs, Daisy; Price, Olivia; Grebely, Jason; Larney, Sarah; Sutherland, Rachel; Read, Phillip; Butler, Kerryn; Degenhardt, Louisa; Peacock, Amy
Abstract: Background: Understanding factors associated with engagement across the hepatitis C virus (HCV) cascade of care (CoC) among people who inject drugs (PWID) is critical for developing targeted interventions to enhance engagement and further HCV elimination efforts. We describe the CoC among Australian PWID, and identify factors associated with engagement at each stage. Methods: As part of the 2018 and 2019 Illicit Drug Reporting System, Australians who regularly inject drugs reported lifetime HCV antibody and RNA testing, treatment uptake and completion. Multivariable logistic regression identified characteristics associated with outcomes. Results: Of 1499 participants, 87% reported antibody testing. Of those, 70% reported RNA testing, of whom 60% reported being RNA positive. Among those, 76% reported initiating treatment, 78% of whom completed. Incarceration history (adjusted odds ratio 1.90; 95% confidence interval 1.28–2.82), current opioid agonist treatment (OAT) (1.99; 1.14–3.47), and recent alcohol and other drug (AOD) counselling (2.22; 1.27–3.88) were associated with antibody testing. Incarceration history (1.42; 1.07–1.87), and current OAT (2.07; 1.51–2.86) were associated with RNA testing. Current OAT (1.92; 1.22–3.03) and recent AOD counselling (1.91; 1.16–3.13) were associated with treatment uptake. Methamphetamine as drug injected most often in the last month was associated with reduced odds of antibody (0.41; 0.25–0.66) and RNA testing (0.54; 0.40–0.74), compared to heroin. Conclusion: CoC engagement amongst Australian PWID is encouraging, with AOD service engagement associated with testing and treatment. Further efforts to reach those not service engaged, particularly those not receiving OAT or who predominantly inject methamphetamine, are needed to achieve HCV elimination targets. Highlights: HCV antibody testing, RNA testing, and treatment for HCV were high amongst this sample of PWID in Australia. AOD service engagement associated with increased HCV testing and treatment uptake. Efforts required to improve reach of testing to those less service engaged, particularly people who inject methamphetamine.